Terrores e mistérios da adolescência e juventude: uma análise da preferência dos jovens pela história de terror - Perrotta, Mari-Pepa Vicente (1988)
Divided in to three main parts, this discourse intends to point out the relations between the young’s pleasure for horror stories and Educational Psychology.